Fasilitas Keselamatan Pada Halte Transjogja - Romadhona, Prima Juanita (Warta Penelitian Perhubungan, 2011)
Nowadays, Bus Rapit Transit (BRT) is favourite mode of transportation in most countries in the world. One of the BRT implementation in indonesia is Trans Jogja at Yogyakarta. As the the entry place and the place for delivering or transfering the passenger, halte should has safety facilities as a safety guarantee for the passenger. In accordance with quantitative analysis by BRT standart requirement, there are 3 facilities from some minimal safety facilities requirements that already installed but not meet the determinant such as transfer access, shelter width, and ramp. In the other hand, there are no safety apparatus at the shelter such as CCTV fire extinguisher and first aid. Keywords: Bus Rapid Transit, Trans Jogja, safety facilities